Increasing oilseed productivity through inclusion of mustard in T. Aman- fallow-boro rice cropping pattern in Jashore (Bangladesh Journal of Agricultural Research, 2026)
The field experiment was conducted at Mahmudkati, Monirampur under Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Jashore for two consecutive years of 2021-22 and 2022-23 through inclusion of mustard var. BARI Sarisha-14 in the fallow period and to study the comparative agronomic performance economic return, increasing cropping intensity, productivity and land use efficiency. The experiment was laid out in a randomized complete block design (RCBD) with ten dispersed replications. Three crops pattern (T. Aman rice –Mustard - Boro rice) and farmers’ existing pattern (T.Aman- fallow- Boro) as control were tested.Two years mean data showed that the improved management practices provided higher yield in improved pattern. Average higher rice equivalent yield (REY), (20.22 t ha-1) production efficiency (59.92 kg ha-1 day-1) and 92.88% land utilization indexwas found in the improved cropping pattern in both years. Gross return of the improved pattern was Tk..711010 ha-1 which was more than 68.24% higher than farmer’s pattern of Tk. 422615 ha-1. Gross margin (Tk. 483610 ha-1) and MBCR (2.13) were also higher in improved cropping pattern in both years than existing pattern.Bangladesh J. Agril. Res. 48(1): 125-136, March 2023